Influence of ROI selection on resting state functional connectivity: an individualized approach for resting state fMRI analysis - Sohn, William S.; Yoo, Kwangsun; Lee, Young-Beom; Seo, Sang W.; Na, Duk L.; Jeong, Yong (Frontiers in Neuroscience, 2015)
The differences in how our brain is connected are often thought to reflect the differences in our individual personalities and cognitive abilities. Individual differences in brain connectivity has long been recognized in the neuroscience community however it has yet to manifest itself in the methodology of resting state analysis. This is evident as previous studies use the same region of interest (ROIs) for all subjects. In this paper we demonstrate that the use of ROIs which are standardized across individuals leads to inaccurate calculations of functional connectivity. We also show that this problem can be addressed by taking an individualized approach by using subject-specific ROIs. Finally we show that ROI selection can affect the way we interpret our data by showing different changes in functional connectivity with ageing.